Differential Regulation of NK Cell Receptors in Acute Lymphoblastic Leukemia. (23rd May 2022) - Lee, Le Jie; Hassan, Norfarazieda; Idris, Siti Zuleha; Subbiah, Suresh Kumar; Seow, Heng Fong; Mohtaruddin, Norhafizah; Chang, Kian Meng; Osman, Raudhawati; Ibrahim, Hishamshah Mohd; Nathan, Sheila; Abdullah, Maha
Abstract : Cancer immunotherapies are preferred over conventional treatments which are highly cytotoxic to normal cells. Focus has been on T cells but natural killer (NK) cells have equal potential. Concepts in cancer control and influence of sex require further investigation to improve successful mobilization of immune cells in cancer patients. Acute lymphoblastic leukemia (ALL) is a hematological malignancy mainly of B cell (B-ALL) and T cell (T-ALL) subtypes. Influence of ALL on NK cell is still unclear. Targeted next-generation sequencing was conducted on 62 activating/inhibitory receptors, ligands, effector, and exhaustion molecules on T-ALL (6 males) and normal controls (NC) (4 males and 4 females). Quantitative PCR (q-PCR) further investigated copy number variation (CNV), methylation index (MI), and mRNA expression of significant genes in T-ALL (14 males), NC (12 males and 12 females), and B-ALL samples (N = 12 males and 12 females). Bioinformatics revealed unique variants particularly rs2253849 (T>C) in KLRC1 and rs1141715 (A>G) in KLRC2 only among T-ALL (allele frequency 0.8-1.0). Gene amplification was highest in female B-ALL compared to male B-ALL ( KLRC2, KLRC4, and NCR3, p < 0.05 ) and lowest in male T-ALL cumulating in deletion of KLRD1 and CD69 . MI was higher in male ALL of both subtypes compared to normal ( KIR2DL1-2 and 4 and KIR2DS2 and 4, p < 0.05 ) as well as to female B-ALL ( KIR3DL2 and KIR2DS2, p < 0.05 ). mRNA expressions were low. Thus, ALL subtypes potentially regulated NK cell suppression by different mechanisms which should be considered in future immunotherapies for ALL.